Preparation and characterisation of inorganic nanostructured support materials for polymer electrolyte fuel cells - September, Caelin Gee (Department of Chemical Engineering, 2016)
Polymer electrolyte fuel cells (PEFCs) have been identified as a safe, clean and reliable alternative energy conversion technology to conventional, fossil fuel based, ones. However, the hindrance to worldwide commercialisation of this technology lies in the poor durability and high costs associated with the current carbon supported platinum (Pt/C) catalysts. Carbon support corrosion and Pt dissolution/aggregation on the catalyst layer within the fuel cell have been confirmed as the major contributors to the degradation of the Pt/C (Shao, et al., 2007). Attention needs to be paid to the improvement of catalyst components to produce an electrocatalyst with better degradation resistance and low Pt loading in order to overcome these two major commercialisation barriers. The physico-chemical and electronic interaction between the Pt catalyst and the support material play a crucial role in the catalytic activity and stability of the electrocatalysts (Wang, et al., 2011). A comprehensive understanding of the effects of catalyst support material and morphology on the mechanism and kinetics of the oxygen reduction reaction (ORR) needs to be developed. This study investigated alternative, novel catalyst support materials and structures for the catalyst layer as opposed to carbon for PEFC applications. This material consisted of TiB2 electrospun nanofibers, powder and crushed electrospun nanofibers. Methods used to reliably and accurately deposit Pt onto these materials were identified, developed and analysed. These methods include platinum deposited onto TiB2 powder, electrospun crushed nanofibers and nanofiber mats via DC magnetron sputter deposition and thermally induced chemical deposition (TICD). The synthesised catalysts were physically characterised using X-ray diffraction (XRD), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM) and Inductively Coupled Plasma Optical emission spectrometry (ICP-OES). Platinum effectively deposited on the TiB2 support structures via these deposition techniques within two standard deviations of the desired Pt loadings.